Edukasi Jajanan Sehat Dan Skrining Kesehatan Bagi Siswa SMP/SMA Al Husna Di Kemilimg Bandar Lampung - Yulyuswarni Yulyuswarni; Isnenia Isnenia (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2026)
The consumption of snacks among school-aged children has become a serious concern in public health due to the widespread use of hazardous food additives such as formalin, borax, Rhodamine B, and excessive artificial sweeteners. These substances are commonly found in food sold around schools and have the potential to cause metabolic disorders, organ damage, and an increased risk of non-communicable diseases. The low level of knowledge among students, teachers, and canteen managers regarding food safety and balanced nutrition exacerbates this condition. This community service activity aims to increase students' knowledge about healthy snacks and encourage early detection through simple health checks. This program was conducted at SMP/SMA Al-Husna Kemiling, Bandar Lampung, involving 20 students, 4 teachers, and 1 canteen manager. The results of the activity show an increase in knowledge among 95% of participants after the education, based on the posttest results. Most participants experienced an increase in scores of 10–50 points from the pretest. The lecture method supported by teaching aids proved effective in helping students understand the material provided.